Propuesta De Conectividad Ecológica Para La Conservación De Los Abejorros Polinizadores Bombus Sp., En El Sector Palacios Del Parque Nacional Natural Chingaza (2023)
This research focused on the identification of areas of impact on the continuity of the vegetation covers, reducing the ecological connectivity and the distribution and mobility of the Bombus sp bumblebees in the Palacios sector of the Chingaza National Natural Park, with the main objective of preserving These pollinators play a vital role in the conservation of biodiversity and the balance of paramo ecosystems. To achieve this purpose, a fundamental tool was used, such as geographic information systems through the lowest energy cost approach. Variables such as vegetation cover (Fragmentation Index and Nontree Vegetation Index), road infrastructure (Distance to roads), water availability (Distance to drains), and effects on the soil (Aridity Index) were analyzed, thus determining the areas with greater ecological aptitude of these species, the dispersal capacity was subsequently evaluated based on the resistance matrix that includes the obstacles or challenges that bumblebees face in their movement and finally the lowest cost routes are identified, tracing efficient paths that allow connectivity of bumblebee populations, these routes become an essential resource for planning conservation strategies that will guarantee the survival of this species crucial for the health of ecosystems and biological diversity